A case of atrial septal defect associated with anomalous sinoatrial node artery in pulmonary atresia with intact ventricular septum. Issue 7 (24th May 2021) - Di Candia, Angela; Castaldi, Biagio; Sirico, Domenico; Di Salvo, Giovanni
Abstract: An 11‐year‐old boy affected by pulmonary atresia with intact ventricular septum (AP‐IVS) was listed for percutaneous pulmonary valvuloplasty and closure of multi‐fenestrated atrial septal defect (ASD). Intra‐procedural transesophageal echocardiography arose the suspect of abnormal coronary artery pattern while selective angiography documented a single sinoatrial node artery (SANa) with an unusual retro‐aortic course. As consequence, we proceeded to effectively close the defects with a not self‐centering device placed in the most central side hole. This case supports the hypothesis that sometimes arrhythmic complication during ASD closure procedures might be due to unrecognized injury of the SANa.